2021
DOI: 10.36351/pjo.v37i3.1171
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Suprachoroidal Triamcinolone Injection on Refractory Diabetic Macular Edema

Abstract: Purpose:  To assess the safety and efficacy of supra choroidal triamcinolone injection (SCT) in cases of refractory diabetic macular oedema. Study Design:  Interventional case series. Place and Duration of Study:  Lahore General Hospital, Lahore, from July to December 2019. Methods:  A total of 22 eyes of patients above 18 years of age, with either Type-1 or Type-2 diabetes mellitus and treatment resistant central Diabetic Macular Edema (DME) of 320 um or more (measured on Zeiss Cirrus HD-OCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…17 Local data also support that supra-choroidal drug administration as a safe and effective route of TA injection in cases of resistant diabetic macular edema. 24 Limitations of present study are small sample size and shorter duration of follow-up. Further studies are obligatory to explore the longstanding effectiveness of SCI of TA in cases of resistant DME.…”
Section: Discussionmentioning
confidence: 80%
“…17 Local data also support that supra-choroidal drug administration as a safe and effective route of TA injection in cases of resistant diabetic macular edema. 24 Limitations of present study are small sample size and shorter duration of follow-up. Further studies are obligatory to explore the longstanding effectiveness of SCI of TA in cases of resistant DME.…”
Section: Discussionmentioning
confidence: 80%
“… 8 Most other studies included in this meta-analysis all noted a rise in IOP 1 and 3 months after injecting suprachoroidal triamcinolone but interestingly, this rise was not statistically significant and was associated with a p -value >0.05. 9 10 , 22 26 The exceptions to this were the studies by Abdelshafy Tabl et al and Ateeq et al . Abdelshafy Tabl et al .’s study was the only study conducted solely in patients with refractory diabetic macular oedema due to epiretinal membrane, and they found a decrease in IOP 1 month after injection.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have shown the efficacy and safety of utilizing suprachoroidal triamcinolone acetonide injection for DME. For example, in an interventional case series [ 28 ], 22 eyes with refractory DME were evaluated. Those eyes were managed with a suprachoroidal injection of triamcinolone acetonide, followed up for three months, and it was concluded that suprachoroidal injection of triamcinolone acetonide for refractory DME is safe and effective.…”
Section: Discussionmentioning
confidence: 99%